1949
DOI: 10.1021/ie50476a035
|View full text |Cite
|
Sign up to set email alerts
|

Titanium and Zirconium Corrosion Studies

Abstract: were encountered. Under tank condibions the ycast was subject t o variation or degeneration and yielded substrains which did not produce riboflavin. A larger inoculum was required since this organism did not grow as rapidly as Candida guillieimondiu, Therefore a new medium was developed to obtain vigorous growth in the inoculum phase. The composition of t,his medium was as fo1lon.s: Sucrose 40 grams per liter Defatted soya flour (trypsin 10 grams per liter Calcium carbonate 5 grams per liter digested 2 hours a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

1950
1950
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 1 publication
2
16
0
Order By: Relevance
“…The apparatus used in these tests conforms to the recommendations of the American Society for Testing Materials as contained in the Tentative Method of Total Immersion Corrosion Tests of Nonferrous Metals (1). A detailed description of the apparatus is contained in previously published papers (6,8). Aeration was supplied either b>7 compressed air from the laboratory air line, or by cylinder nitrogen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The apparatus used in these tests conforms to the recommendations of the American Society for Testing Materials as contained in the Tentative Method of Total Immersion Corrosion Tests of Nonferrous Metals (1). A detailed description of the apparatus is contained in previously published papers (6,8). Aeration was supplied either b>7 compressed air from the laboratory air line, or by cylinder nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…The important pollutants of the Los Angeles atmosphere and their concentrations listed in Table I are representative of air sampling data obtained during clear and smog periods (10). Investigations covering these contaminants have led to a number of conclusions regarding the causes of the characteristic haze that often reduces visibility to less than 1 mile (11, IB), the causes of gas damage to vegetation (B, 8, 8), the nature of the eye-irritating materials (6), and the high rate of rubber cracking (6,7). A complete discussion of these experimental studies is beyond the scope of this paper.…”
Section: Methodsmentioning
confidence: 99%
“…It is not a durable material, however, when exposed to sulfuric or hydrochloric acids. At 100~ it is reported that 3 per cent HC1 corrodes titanium at a rate of about 1700 mdd (0.5 ipy) (1). Stainless steels of the 18 per cent Cr, 8 per cent Ni variety (18-8) are also attacked by these acids, but, in the case of sulfuric acid, the corrosion rate can be substantially reduced by small additions of ferric or cupric sulfates.…”
Section: Introductionmentioning
confidence: 99%
“…For this, cleaned asreceived Ti foils were treated with H 2 O 2 under high reaction rate conditions (high temperature, limited period of time) and low reaction rate conditions (room temperature, long period of time) or the same treatments were carried out on Ti foils previously treated with 30% nitric acid (HNO 3 ), a well-known passivating agent for Ti. 9 Surprisingly, despite an obvious surface area increase with H 2 O 2 treatments, the best performance enhancement of the back-illuminated DSSC was achieved using only the simple HNO 3 treatment. No laborious chemical etching or polishing pre-treatments are necessary.…”
mentioning
confidence: 94%